Preliminary experimental study on effectiveness of aquatic vegetation on sediment transport capacity - Nordila Ahmad,; Zuliziana Suif,; Maidiana Othman,; Wan Mohamed Syafuan Wan Mohamed Sabri,; Muhamad Azani Yahya,; Ahmad Naqiuddin Azha, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Vegetation affects sediment transport by obstructing the flow and changing the turbulence characteristics. Common sediment transport equations are not applicable to situations with submerged vegetation. A laboratory experiment was carried out in which flow, vegetation, and sediment transport were measured in an open channel model with a 240 cm long section of 50 cm high x 50cm width with submerged vege-tation in a sand bed. Measured data from various vegetation density and height were analyzed to obtain estimates of the trapping efficiency. Results show an increment of the trapping efficiency with 86.7% and 94.2% reduction in sediment concentration compared to a case without vegetation.